A Rare Case of Oligodendroglioma in Sacrococcygeal Mature Teratoma Diagnosed in Preterm Infant - Mun Hui Jeong; Seong Hee Jeong; Chung Su Hwang; Yong-Hoon Cho; Shin-Yun Byun; Narae Lee (Korean Society of Neonatology, 2022)
Sacrococcygeal teratoma is the most common congenital tumor in neonates, and is reported in approximately 1/35,000 to 1/40,000 live births. Oligodendroglioma is a rare central nervous system tumor that is usually found in the cerebral hemisphere of young and middle aged adults. When associated with a teratoma, it is mainly identified in ovarian teratoma in adolescents and adults. We describe a rare case of a preterm infant with oligodendroglioma in a mature sacrococcygeal teratoma. The male neonate was born at a gestational age of 30 weeks with a protruding mass in the sacrococcygeal region. Pelvic magnetic resonance imaging showed a sacrococcygeal teratoma of approximately 11 cm comprising fat components and skeletal structure, that extended from the anterior part of the sacrum to the abdominal cavity. Radical resection was performed at 36 days of age. Macroscopically, the resected intra-abdominal mass had the characteristics of a cystic lesion, and the intrapelvic mass was a predominantly solid mixed cystic-solid lesion. Histologically, this solid lesion in the intrapelvic mass was composed of mature glial tissue, which comprised as a proliferation of monotonous cells with small and round nuclei, surrounded by a perinuclear halo ("fried egg" appearance). Additionally, these cells were immunohistochemically positive for glial fibrillary acidic protein. These findings confirmed the diagnosis of oligodendroglioma in sacrococcygeal mature teratoma. After the treatment, no recurrence was observed during the follow-up period, and no additional intervention was required. However, the patient is undergoing treatment for voiding dysfunction caused by a neurogenic bladder.